Gulllain-Barre Syndrome After Trivalent Influenza Vaccination in Adults - Chang, Kuo-Hsuan; Lyu, Rong-Kuo; Lin, Wan-Ting; Huang, Yu-Tung; Lin, Huang-Shen; Chang, Shang-Hung (Frontiers in Neurology, 2019)
Lines of evidence suggest trivalent influenza vaccination may be associated with Guillain-Barre syndrome (GBS), an immune-mediated acute inflammatory neuropathy. On the other hand, this vaccination protects against influenza infection, which has been demonstrated as a trigger of GBS. To clarify the net effect of trivalent influenza vaccines on GBS, we conducted a retrospective nationwide nested case-control study using the database of the Taiwan National Health Insurance program. We identified 182 hospitalized patients with GBS aged ≥ 50 years from 2007 to 2016 as the cases, and 910 hospitalized patients, matched by gender, age, date of hospitalization, comorbidities and medications, as the control subjects. Nearby and remote exposures of vaccination were defined as subjects who had received trivalent influenza vaccine 42 (nearby exposure) and 90 days (remote exposure) before the date of hospitalization, respectively. We found 7 (3.85%) GBS patients and 26 (2.86%) matched control subjects demonstrated nearby exposures of influenza vaccine (odds ratio: 1.46, 95% confidence interval: 0.56 ~ 3.78). Seventeen (9.34%) GBS patients exposed to influenza vaccines remotely, while the number of remote exposure of influenza vaccines in matched control subjects was 72 (7.91%, odds ratio: 1.26, 95% confidence interval: 0.67 ~ 2.38). These results do not support an association between trivalent influenza vaccine and GBS among the patients aged ≥ 50 years.